Hepatoblastoma and Wilms' tumour in an infant with Beckwith–Wiedemann syndrome and diazoxide resistant congenital hyperinsulinism. (27th February 2019) - Uppal, Saurabh; Blackburn, James; Didi, Mohammed; Shukla, Rajeev; Hayden, James; Senniappan, Senthil
Summary: Beckwith–Wiedemann syndrome (BWS) can be associated with embryonal tumours and congenital hyperinsulinism (CHI). We present an infant with BWS who developed congenital hepatoblastoma and Wilms' tumour during infancy. The infant presented with recurrent hypoglycaemia requiring high intravenous glucose infusion and was biochemically confirmed to have CHI. He was resistant to diazoxide but responded well to octreotide and was switched to Lanreotide at 1 year of age. Genetic analysis for mutations of ABCC8 and KCNJ11 were negative. He had clinical features suggestive of BWS. Methylation-sensitive multiplex ligation-dependent probe amplification revealed hypomethylation at KCNQ1OT1:TSS-DMR and hypermethylation at H19 /IGF2:IG-DMR consistent with mosaic UPD(11p15). Hepatoblastoma was detected on day 4 of life, which was resistant to chemotherapy, requiring surgical resection. He developed Wilms' tumour at 3 months of age, which also showed poor response to induction chemotherapy with vincristine and actinomycin D. Surgical resection of Wilms' tumour was followed by post-operative chemotherapy intensified with cycles containing cyclophosphamide, doxorubicin, carboplatin and etoposide, in addition to receiving flank radiotherapy. We report, for the first time, an uncommon association of hepatoblastoma and Wilms' tumour in BWS in early infancy. Early onset tumours may show resistance to chemotherapy. UPD(11p15) is likely associated with persistent CHI in BWS. Learning points: Long-acting somatostatin analogues are effective in managing persistent CHI in BWS. UPD(11)pat genotype may be a pointer to persistent and severe CHI. Hepatoblastoma and Wilms' tumour may have an onset within early infancy and early tumour surveillance is essential. Tumours associated with earlier onset may be resistant to recognised first-line chemotherapy.